Controlling the Morphology in Electrostatic Self-Assembly via Light - Agarwal, Mohit; Zika, Alexander; Schweins, Ralf; Gröhn, Franziska (Polymers, 2024)
Electrostatic self-assembly of macroions is an emerging area with great potential in the development of nanoscale functional objects, where photo-irradiation responsiveness can either elevate or suppress the self-assembly. The ability to control the size and shape of macroion assemblies would greatly facilitate the fabrication of desired nano-objects that can be harnessed in various applications such as catalysis, drug delivery, bio-sensors, and actuators. Here, we demonstrate that a polyelectrolyte with a size of 5 nm and multivalent counterions with a size of 1 nm can produce well-defined nanostructures ranging in size from 10–1000 nm in an aqueous environment by utilizing the concept of electrostatic self-assembly and other intermolecular non-covalent interactions including dipole–dipole interactions. The pH- and photoresponsiveness of polyelectrolytes and azo dyes provide diverse parameters to tune the nanostructures. Our findings demonstrate a facile approach to fabricating and manipulating self-assembled nanoparticles using light and neutron scattering techniques.
CRIS-Team Scopus Importer:2024-01-19
Keywords: electrostatic assembly; kinetically controlled; light irradiation; nanostructures; polyelectrolyte; thermodynamically controlled

Double-Wavelength-Switchable Molecular Self-Assembly of a Photoacid and Spirooxazine in an Aqueous Solution - Zika, Alexander; Agarwal, Mohit; Schweins, Ralf; Gröhn, Franziska (Journal of Physical Chemistry Letters, 2023)
Quadruple-switchable nanoscale assemblies are built by combining two types of water-soluble molecular photoswitches through dipole-dipole interaction. Uniting the wavelength-specific proton dissociation of a photoacid and ring-opening of an anionic spirooxazine results in an assembly that can be addressed by irradiation with two different wavelengths: pH and darkness.
CRIS-Team Scopus Importer:2023-11-17

Joining Two Switches in One Nano-Object: Photoacidity and Photoisomerization in Electrostatic Self-Assembly - Zika, Alexander; Agarwal, Mohit; Schweins, Ralf; Gröhn, Franziska (Chemistry - A European Journal, 2022)
Multi-switchable supramolecular nano-objects that respond to irradiation of different wavelengths with changes in size and shape have been built from two different water-soluble molecular switches, joined by attachment to the same polyelectrolyte. Accordingly, two wavelength-specific reactions, namely the excited-state proton dissociation of a photoacid and the cis-trans isomerization of an azo dye, are combined in one supramolecular nano-object that is stable in aqueous solution. The concept has potential in the fields of sensors, molecular motors, and transport.
CRIS-Team WoS Importer:2023-01-27

Photoacid-macroion assemblies: how photo-excitation switches the size of nano-objects - Zika, Alexander; Agarwal, Mohit; Zika, Wiebke; Guldi, Dirk Michael; Schweins, Ralf; Gröhn, Franziska (Nanoscale, 2023)
Electrostatic self-assembly of photoacids with oppositely charged macroions yields supramolecular nano-objects in aqueous solutions, whose size is controlled through light irradiation. Nano-assemblies are formed due to electrostatic attractions and mutual hydrogen bonding of the photoacids. Irradiation with UV light leads to the deprotonation of the photoacid and, consequently, a change in particle size. Overall, the hydrodynamic radii of the well-defined photoacid-macroion nano-objects lie between 130 and 370 nm. For a set of photoacids, we determine the acidity constants in the ground and excited state, discuss the sizes of photoacid-macroion nano-objects (by dynamic and static light scattering), their composition and the particle shapes (by small-angle neutron scattering), and relate their charge characteristics to size, structure and shape. We investigate the association thermodynamics and relate nanoscale structures to thermodynamics and, in turn, thermodynamics to molecular features, particularly the ionization energy of the photoacid hydroxyl group proton. Structure-directing effects completely differ from those for previously investigated systems, with hydrogen bonding and entropic effects playing a major role herein. This combined approach allows developing a comprehensive understanding of assembly formation and photo-response, anchored in molecular parameters (pKa, ionization energy, substituent group location), charge characteristics, and the association enthalpy and entropy. This fundamental understanding again paves the way for tailoring application solutions with novel photoresponsive materials.
CRIS-Team Scopus Importer:2023-12-29

Solvent Induced Helix Folding of Defined Indolenine Squaraine Oligomers - Turkin, Arthur; Holzapfel, Marco; Agarwal, Mohit; Fischermeier, David; Mitric, Roland; Schweins, Ralf; Gröhn, Franziska; Lambert, Christoph (Chemistry - A European Journal, 2021)
A protecting group strategy was employed to synthesise a series of indolenine squaraine dye oligomers up to the nonamer. The longer oligomers show a distinct solvent dependence of the absorption spectra, that is, either a strong blue shift or a strong red shift of the lowest energy bands in the near infrared spectral region. This behaviour is explained by exciton coupling theory as being due to H- or J-type coupling of transition moments. The H-type coupling is a consequence of a helix folding in solvents with a small Hansen dispersity index. DOSY NMR, small angle neutron scattering (SANS), quantum chemical and force field calculations agree upon a helix structure with an unusually large pitch and open voids that are filled with solvent molecules, thereby forming a kind of clathrate. The thermodynamic parameters of the folding process were determined by temperature dependent optical absorption spectra.
CRIS-Team Scopus Importer:2021-05-21
Keywords: dye chemistry; solvent effects; superstructure; supramolecular folding; UV/Vis spectroscopy

The Role of Light Irradiation and Dendrimer Generation in Directing Electrostatic Self-Assembly - Agarwal, Mohit; Zika, Alexander; Yücel, Müge; Schweins, Ralf; Kohlbrecher, Joachim; Gröhn, Franziska (Polymers, 2025)
pH-responsive polyamidoamine (PAMAM) dendrimers are used as well-defined building blocks to design light-switchable nano-assemblies in solution. The complex interplay between the photoresponsive di-anionic azo dye Acid Yellow 38 (AY38) and the cationic PAMAM dendrimers of different generations is presented in this study. Electrostatic self-assembly involving secondary dipole–dipole interactions provides well-defined assemblies within a broad size range (10 nm–1 μm) with various shapes. The size and shape of these assemblies were determined using dynamic and static light scattering (DLS/SLS) and small-angle neutron scattering (SANS); ζ-potential measurements were performed to elucidate the charge characteristics, revealing the effective surface charge density of the nano-objects as an important parameter in the size and shape control. UV–vis spectroscopy and isothermal titration calorimetry (ITC) were employed to investigate the interaction on a molecular level and from a thermodynamic point of view. The results show that the amount of isomerized cis dye depends on the dendrimer generation because of a photoprotective effect through electrostatics for lower generations and through dipole–dipole interactions for higher generations; as the cis dye and trans dye bind with different strength, the amount of cis dye then again encodes the charge density and thereby the particle size and shape.
CRIS-Team Scopus Importer:2025-01-31
Keywords: azo dye; dendrimer; electrostatic self-assembly; light irradiation; photoresponsive; switchability